Gait Characteristics and Effects of Early Treadmill Intervention in Infants and Toddlers with Down Syndrome: A Systematic Review - Kınacı-Biber, Esra; ÖNERGE, KÜBRA; Mutlu, Akmer (Taylor & Francis Ltd., 2022)
Purpose The aim of this study was to evaluate gait characteristics, and the effectiveness of treadmill interventions on gait in infants and toddlers with Down syndrome (DS). Materials and Methods A comprehensive search was performed on six databases for evidence published up to November 2020 for articles related to infants and toddlers with DS. The Clinical Appraisal Skills Programme Checklist assessed the methodological quality. Strength of evidence were evaluated Sackett's level. Results Nine articles analyzing instrumental gait met the inclusion criteria. Of these, 4 compared DS and typically developing (TD), and 5 included treadmill training interventions for DS. Kinematic analysis was applied in 8 studies and all articles presented evaluations at different times according to the walking experience. Analysis with EMG was used in only one of the intervention articles and in 3 of the 4 comparative articles. Conclusions Although similar improvements are seen in spatiotemporal parameters for toddlers with typical development and those with DS, the decrease in step width is not similar for DS. Early treadmill training can have a positively effect on the gait characteristics of DS infants. Further research should focus on the acquisition of gait characteristics, long-term evaluations, kinetics and EMG data, for these children.
Keywords: Down Syndrome; Gait Analysis; Gait Characteristics; Treadmill Training; Rehabilitation